Autoavaliação institucional em Instituição de Ensino Superior no Ceará, na perspectiva da comunidade acadêmica - Martins, Alexciano de Sousa (2017)
We seek, more and more, quality in everything that is offered to society. In the field of Higher Education in Brazil, it is no different. Since the publication of Law No. 10,861 of April 14, 2004, which established the National System for the Evaluation of Higher Education (SINAES), evaluation is one of the instruments capable of measuring the level at which courses need to be improved. Since the SINAES has two external evaluations and an internal and permanent one called Institutional Self-Assessment (AI), the system seeks to identify, in its three large dimensions, didactic-pedagogical organization, infrastructure and faculty and tutorial, aspects that need to be improved in the courses and in the Higher education institutions (HEIs). AI is recurring in academia, but what remains to know is whether its results provide the expected changes in real time. The exploratory study of two cases studied here analyzes the IIA of two IFCE campuses, aiming at knowing the institutional self-assessment of a Higher Education institution, the IFCE, from the perspectives of students, technicians and teachers, in order to verify the effectiveness of Improvements in courses and in the Institution, from 2014 to 2016, resulting from this evaluation process. The subjects studied were the managers, students, teachers and technicians in Education of the campuses of Tauá and Crateús, in Ceará. The field data collection was performed through a structured interview with the managers, then a specific questionnaire for each respondent segment of the institutional self-assessment, being thus characterized as an exploratory field research. Complementing the data collection, the Central Evaluation Commission was heard and the information collected was compared with an earlier study in the same HE with a similar theme. It was noted that managers use the AI ​​data to perform their interventions on the campuses, even without being systematized with planning. Regarding the segments, it is possible to verify that in some aspects researched and considered weaknesses in the AI, the technicians, students and teachers of this study were able to perceive improvements in the HEI, such as investments in infrastructure, increase in the number of servers, extension programs. Not always, however, the actions of the management to overcome the weaknesses pointed out in the AI ​​are perceived or satisfied by the administrative technicians, teachers and students, since they point out aspects that do not denote any improvement. Finally, some results of this study should be relativized due to server turnover and some specificities of the institutional self-assessment questionnaires.